2007
DOI: 10.1001/archsurg.142.10.969
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and Risk Factors of Complications After Gastric Bypass

Abstract: Main Outcome Measures: Complications were stratified by grade: grade I, only bedside procedure; grade II, therapeutic intervention but without lasting disability; grade III, irreversible deficits; and grade IV, death. Data were analyzed using logistic regression to identify independent risk factors of complications after GBP. Predictors investigated were age, race, sex, marital and insurance status, body mass index, obesity-associated comorbidities, American Society of Anesthesiologists Physical Status Class, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 55 publications
0
37
2
3
Order By: Relevance
“…A total number of 20 articles entered the meta-analysis models (fig. 1) [24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]. …”
Section: Resultsmentioning
confidence: 99%
“…A total number of 20 articles entered the meta-analysis models (fig. 1) [24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are no standardized techniques to account for the different body shapes of the morbidly obese patient. These two factors resulted in increased operative time and complication rate [5][6][7]. We showed that XU distance was predictive of a challenging operation.…”
Section: Discussionmentioning
confidence: 77%
“…Whereas the focus on the development of GJ strictures centers mostly on technical aspects, the underlying mechanism for the development of marginal ulcers has not been clearly defined. Several studies suggest ischemia, increased gastric acid, foreign-body reaction, H. pylori infection, smoking, and NSAID use as contributing factors for the development of this complication [18,23,28,36,[38][39][40]. It is postulated that staples or suture material used to create the GJ leads to an intense inflammatory reaction with mucosal breakdown.…”
Section: Discussionmentioning
confidence: 99%